Leadership, Management, and Performance: Examining three key roles in construction project safety in Banten, Indonesia : . - Eten Hilman Hartono; Ika Nurul Qamari (CV. Sakura Digital Nusantara, 2026)
Purpose – Despite existing occupational safety regulations, Indonesia’s construction industry continues to experience a high incidence of workplace accidents. This study examines the mediating role of safety management in the relationship between safety leadership and safety performance in construction projects. Approach – An explanatory quantitative design was employed involving 174 construction project personnel in Banten Province, Indonesia, selected through purposive sampling. Data were collected using a seven-point Likert-scale questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM). Findings/Results – Safety leadership had significant positive effects on both safety management and safety performance. Safety management also positively influenced safety performance and significantly mediated the relationship between safety leadership and safety performance. Originality/Value – This study provides empirical evidence of safety management as a mechanism through which safety leadership improves safety performance in the Indonesian construction sector. The findings indicate that leadership commitment alone may not be sufficient without effective safety management practices. Construction companies should therefore integrate strong safety leadership with systematic safety management to improve safety performance and reduce workplace accident risks.